Large Hole Rotary Drill Performance (c77e5de0-de67-47fa-9ab6-1a7cb81cfd58) - J Lyall Workman; Peter N. Calder (International Society of Explosives Engineers, 1996)
Large hole rotary drilling is one of the most common methods of producing blastholes in open pit mining. Large hole drilling generally refers to diameters from 9 to 17 inch (229 to 432 mm), however a considerable amount of rotary drilling is done in diameters from 6½ to 9 inch (165 to 229 mm). These smaller diameters are especially prevalent in gold mining and quarrying.